Transformational Leadership and its Influence on Building a Culture of Innovation within Technology Firms - Wijaya, Wijaya; Akhtar, Shazia; Khan, Jamil; Sijabat, Saut Gracer (Journal of Loomingulisus ja Innovatsioon, 2025)
Innovation has become a defining factor for organizational survival and competitiveness in the technology sector, where dynamic markets demand continuous adaptation and creativity. This study aims to examine the relationship between transformational leadership practices and the development of a culture of innovation within technology firms. A quantitative research design was employed using a cross-sectional survey distributed to 320 employees across ten leading technology companies in Southeast Asia. The Transformational Leadership Inventory (TLI) and Innovation Climate Scale (ICS) were utilized to assess leadership behavior and organizational culture, respectively. Statistical analyses, including structural equation modeling (SEM), revealed a strong positive correlation (r = 0.74, p < 0.01) between transformational leadership dimensions particularly intellectual stimulation and inspirational motivation and innovation culture indices. The findings indicate that leaders who encourage risk-taking, empower employees, and communicate a shared vision significantly enhance creativity and collective learning. The study concludes that transformational leadership serves as a critical driver in shaping an organizational climate conducive to innovation, underscoring the need for leadership development strategies centered on creativity and adaptability.